KONTRIBUSI CREATIVE DANCE DALAM KEGIATAN WORKSHOP CIPTA KARYA LAGU DAN SASTRA ANAK BERBASIS KEARIFAN LOKAL SEBAGAI MEDIA PENDIDIKAN - Dyan Indah Purnama; Destrine Megentina (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2022)
Creative Dance is a way to learn how to create dance moves creatively.  Creative Dance also contributes to providing experiences in creating dances based on songs that have been created by participants in workshops on songwriting and children's literature based on local wisdom as an educational medium.  This activity is one of a series of activities to welcome the 100th anniversary of the birth of the Tamansiswa College.  This activity aims to provide training to increase understanding as well as experience in implementing the Sariswara method as a typical Tamansiswa artistic method in schools.  The Sariswara method itself can be integrated with several lesson content and collaborate with local cultural objects. The benefits to Tamansiswa Pamong and public school teachers and provide confidence so that they do not feel taboo in using this method in the class, as was done by Ki Hadjar Dewantara.  Workshop participants are Tamansiswa Pamong and public school teachers, totaling approximately 80 participants, this activity was carried out for 3 days and 2 nights at the Grage Ramayana Hotel.  The method used is descriptive qualitative, to describe the condition of the data as it is, through a process of observation, interviews, and documentation.  Through this research, it is hoped that it can provide understanding and experience in creating simple dance moves through songs that were created independently to the Tamansiswa administrators and also public school teachers who attend workshops on creating songs and children's literature based on local wisdom as a medium of education.